Effect of climate change on Oriental fruit fly in New Zealand and the Pacific - Kriticos, D.J.; Stephens, A.E.A.; Leriche, A. (New Zealand Plant Protection, 2007)
A CLIMEX model of the Oriental fruit fly (OFF) indicates that under the reference climate (19611990) OFF could persist throughout most of the central Pacific In New Zealand it could establish throughout much of the lowlying areas of the North Island and much of New Zealand could support shortterm populations during the summer months Climate change scenarios for the 2080s indicate that in the central Pacific the change in potential distribution is relatively minor However parts of New Zealand could become substantially more climatically suitable increasing the likelihood of successful establishment of OFF after an incursion and seriously threatening the horticultural sector Should OFF become established in New Zealand it is likely to follow any expansion of the horticultural sector into the coastal areas of the eastern part of the South Island as far south as Oamaru